On-line portfolio selection - Li, Bin. (2013)
On-line portfolio selection, aiming to sequentially determine optimal allocations across a set of assets, is a fundamental research problem in computational finance. This thesis investigates this problem by conducting a comprehensive survey and presenting a family of new strategies using machine learning techniques. The major contributions of this thesis are summarized as follows.